Treatment options of human demodicosis - Pawełczyk, Olga (Journal of Education, Health and Sport, 2024)
Background: Human demodicosis is a parasitic disease caused by two species of mites, Demodex folliculorum and Demodex brevis. Cutaneous and ocular demodicosis most often occurs in a situation of impaired immune response, where the attacked organism is weakened, has reduced immunity or metabolic disorders. The treatment of demodicosis can last up to several months and requires a lot of patience and regularity from the patient. Objective: The aim of this paper is to review the therapeutic options used in the treatment of the ocular and cutaneous human demodicosis. Materials and methods: This review was based on available data collected in the PubMed and Google Scholar databases, using the keywords: ‘Demodex brevis’, ‘Demodex folliculorum’, ‘Demodex mite’, ‘human demodicosis treatment’. Conclusions: Treatment of demodicosis based on the use of a single medicament has the lowest efficiency and effectiveness. In contrast, a combination therapies, in which oral and local applied medication are taken together or several types of local medication are combined have the best effect.